Flavored Yogurt Complex Viscosity Influences Real-Time Aroma Release in the Mouth and Sensory Properties - Saint-Eve, Anne; Martin, Nathalie; Guillemin, Hervé; Sémon, Etienne; Guichard, Elisabeth; Souchon, Isabelle (Journal of agricultural and food chemistry, 2006)
The influence of flavored yogurt texture on aroma perception and in-nose aroma release measured by atmospheric pressure chemical ionization mass spectrometry analysis was investigated. The study was carried out on six yogurts varied by protein composition and mechanical treatment. For the same matrix composition, the complex viscosity of yogurts influenced in-nose release and perception. After swallowing, aroma release and intensity of olfactory perception were stronger in low-viscosity yogurts than in high-viscosity yogurts. Moreover, the protein composition influenced aroma release only when yogurts exhibited wide variations of complex viscosity and consequently texture. In mouth, aroma release and perception were influenced more by yogurt mechanical treatment than by protein composition. On the basis of mass transfer analysis, the main physical mechanism which could explain the difference in aroma release would be the surface exchange area developed in the mouth and in the throat. Keywords: Dairy proteins; aroma release; texture; perception; APCI-MS